Effect of liquid urea on growth and yield of grain corn (Zea mays L.) - Md Motasim, Ahmmed; Samsuri, Abd. Wahid; Abdul Sukor, Arina Shairah; Mohd Amin, Adibah (Taylor and Francis Group, 2022)
Efficient nitrogen management is the key strategy for sustainable crop production. A two-season (south-west and north-east monsoon season) experiments were conducted in Ladang 15, Faculty of Agriculture, Universiti Putra Malaysia in 2020 to compare the effect of liquid (LU) and granular urea (GU) on growth and yield of grain corn. The treatments were T0 = No urea (Control), T1 = GU (100%) at 10 days after sowing (DAS) and 28 DAS, T2 = LU (100%) at 10 and 28 DAS, T3 = LU (100%) at 10, 40 and 65 DAS, T4 = LU (50%) at 10 and 28 DAS and T5 = LU (50%) at 10, 40 and 65 DAS. Plant height, stem diameter, ear height and dry grain weight were higher in season 1 (south-west monsoon), but other growth and yield parameters were similar to season 2 (north-east monsoon). The highest cob diameter (5.43 and 5.30 cm), kernel rows/cob (17.30 and 16.72), seeds/row (38.88 and 36.96) and fresh cob weight (325.45 g and 319.18 g) were recorded from T3 and T5 treatments but the highest 100-grain weight resulted in T3 (50.51 g) and T2 (49.02 g) treatments. The highest grain yield (11,019.23 kg/ha) was recorded in T3 treatment. The highest total N content was recorded in T3 (161.92 kg/ha) treatment followed by T2 (141.04 kg/ha). In addition, the highest NUE was recorded in T3 (77.42%) and T5 (75.42%) treatments. As a result, the three splits application of LU was the most efficient application method for maximizing the growth and yield of grain corn.